¿Why use information and communications technology in the process of teaching-learning? (2020)
In this document there are exposed some advantages of the use of information and communication technologies in the process of Teaching-Learning. They stand elements of each of them that support the students and teachers and improve communication in educative contexts. Also they stand the positive impacts inside the classrooms and labor sphere.